When women lead what they achieve, why they succeed, and how we can learn from them - Boorstin, Julia (New York Simon & Schuster, Inc, 2022)
Now, in When Women Lead, Boorstin brings together the stories of over sixty of those female CEOs and leaders, and dozens of new studies. Her combination of narrative and research reveals how once-underestimated characteristics, from vulnerability and gratitude to divergent thinking, can be vital superpowers?and that anyone can work these approaches to their advantage. Featuring new interviews with Katrina Lake, Gwyneth Paltrow, Jenn Hyman, Whitney Wolfe Herd, Lena Waithe, Shivani Siroya, Julia Collins, and more, When Women Lead is a radical blueprint for the future of business, and our world at large.
Includes bibliographical references (pages 375-415) and indexes.
Keywords: Women executives